2019
DOI: 10.1021/acs.iecr.9b00752
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Design for Integrating Lithium-Based Carbon Capture Looping Systems into Natural Gas Combined Cycle Power Plants

Abstract: Lithium orthosilicate (Li 4 SiO 4 ) based sorbents have been reported to show relatively high CO 2 capture capacity and high stability and require lower regeneration temperatures than other high-temperature sorbents. Based on these properties, a capture plant concept could be envisaged, aiming for achieving as low as possible CO 2 capture penalties. Accordingly, this work presents a conceptual AspenPlus process simulation study that evaluates the thermal integration of Li 4 SiO 4 -based looping systems into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Simulation results show that the net efficiency of the plant is reduced by 9.7% points (3.1% points less than the conventional PCC technology). Saleh et al (2019) proposed a novel conceptual NGCC configuration integrated with a lithium-based PCC technology, which shows a reduction in its net efficiency equal to 9.2% points, being this value close to the energy penalty of the amine-based PCC technology published elsewhere (Sanchez Fernandez et al, 2014;Díaz-Herrera et al, 2021). Other studies reported the use of thermal solar energy to compensate for the energy penalty of the PCC plant (Li et al, 2012;Lambert et al, 2014;Wang et al, 2015;Liu et al, 2017;Shirmohammadi et al, 2021).…”
Section: Introductionmentioning
confidence: 70%
“…Simulation results show that the net efficiency of the plant is reduced by 9.7% points (3.1% points less than the conventional PCC technology). Saleh et al (2019) proposed a novel conceptual NGCC configuration integrated with a lithium-based PCC technology, which shows a reduction in its net efficiency equal to 9.2% points, being this value close to the energy penalty of the amine-based PCC technology published elsewhere (Sanchez Fernandez et al, 2014;Díaz-Herrera et al, 2021). Other studies reported the use of thermal solar energy to compensate for the energy penalty of the PCC plant (Li et al, 2012;Lambert et al, 2014;Wang et al, 2015;Liu et al, 2017;Shirmohammadi et al, 2021).…”
Section: Introductionmentioning
confidence: 70%